Cellulosic micelles as nanocapsules of liposoluble CdSe/ZnS quantum dots for bioimaging. Issue 39 (26th September 2016) - Li, Yanpeng; Zhang, Jinming; Guo, Yanzhu; Chen, Meiwan; Wang, Lu; Sun, Runcang; Wang, Xiaohui
Abstract : Sustainable light-emitting nanoaggregates obtained by encapsulating liposoluble CdSe/ZnS QDs in novel cellulosic micelles show promise in bioimaging. Abstract : Nanostructures encapsulating multiple quantum dots (QDs) are of special interests for live cell imaging and biomolecular recognition due to their inherent signal amplification. In this study, a novel type of biomass-based nanomicelles was prepared and characterized for facile loading and solubilization of fluorescent hydrophobic CdSe/ZnS QDs in water. The biobased nanomicelles were formed by the self-assembly of amphiphilic cellulose- graft -poly ( p -dioxanone) (MCC- g -PPDO) synthesized via homogeneous ring-opening polymerization in an ionic liquid. Through a simple physical loading method, multiple lipophilic CdSe/ZnS QDs can be simultaneously encapsulated in one MCC- g -PPDO micelle showing an obviously enlarged micelle size, whereas the loaded QDs exhibited a negligible change in their size and size distribution. The QDs-loaded cellulosic micelles exhibited good optical stability, narrow emission bandwidth as well as an acceptable quantum yield of ∼27%. Successful tumor cell internalization and negligible cytotoxicity were observed with these light-emitting cellulosic micelles. It was found that over 90% of the cells were viable after 24 h of exposure and the fluorescent signal inside the cells reached a maximum after 2 h of exposure. These QDs-loaded cellulosic nanomicelles derived from biomass are a promising candidate for bioimaging or other functional applications.